Warming and grazing enhance litter decomposition and nutrient release independent of litter quality in an alpine meadow. (28th January 2022) - Li, Bowen; Lv, Wangwang; Sun, Jianping; Zhang, Lirong; Jiang, Lili; Zhou, Yang; Liu, Peipei; Hong, Huan; Wang, Qi; A, Wang; Zhang, Suren; Xia, Lu; et al.
Abstract: Warming and grazing, and litter quality jointly determine litter decomposition and nutrient releases in grazing ecosystems. However, their effects have previously been studied in isolation. We conducted a two factorial experiment with asymmetric warming using infrared heaters and moderate grazing in an alpine meadow. Litter samples were collected from all plots in each treatment, among which some subsamples were placed in their original plots and other samples were translocated to other treatment plots to test the relative effects of each treatment on litter decomposition and nutrient releases. We found that warming rather than grazing alone significantly increased total losses of litter mass, total organic carbon, total nitrogen (TN) and total phosphorus (TP) per unit area due to increases in both mass loss rates and litter biomass. However, grazing with warming did not affect their total mass losses because increased mass loss was offset by decreased litter biomass compared with the control. Seasonal mean soil temperature better predicted litter decomposition than litter lignin content or carbon to nitrogen ratio. There were interactions between warming and grazing, but there were no interactions between them and litter quality on litter decomposition. The temperature sensitivity of TN loss was higher than that of TP loss per unit area. Our results suggest that increased temperature has a greater effect on litter decomposition and nutrient release than change in litter quality, and that more N release from litter could result in greater P deficiency in the alpine meadow.